THE ROLE OF HUMOROUS ADVERTISING AND ITS INFLUENCE ON THE DEVELOPMENT OF SOCIAL LIFE (American Journal of Technology and Applied Sciences, 2023)
Based on historical and ethnographic materials, the history and substance of humorous advertising, the function of advertising in various historical eras and societies, and the function of advertising in globalization processes are all examined.